The gun man Jackson Swagger [large type] - Hunter, Stephen, 1946- (Center Point Large Print, 2026)
"In the frying pan of a drought-scorched 1890s Southwest, an old man shows up at the region's only prosperous spread, the Callahan ranch, seeking work. Jack is flinty, shrewd, tough, and a natural with a gun. As an incentive to be taken on at his age, he shows the foreman an uncanny skill with one of Mr. Winchester's latest models. He knows a sharpshooter would be valuable to Colonel Callahan and head gun man Tom Voth. But he has his own mission. Aware that a young cowboy on the ranch has died mysteriously, Jack begins to investigate. He soon realizes that the death and the source of the Callahan wealth are dangerously entwined and that many of the dark forces of the American West are at play on the ranch. Soon enough, it's the season of the six-gun and its fastest shootist."--